Love at 350 Degrees : A Novel - Peers, Lisa (New York : The Dial Press, 2023)
Tori Moore is a popular high school chemistry teacher and avid home baker who longs for something new, especially as she faces an empty nest as a single mom. At the urging of her twin teenagers, she auditions for the American Bake-o-Rama TV competition, telling herself that if she did somehow make it all the way, the prize money could allow her to finally open her own bakery. But still reeling from her divorce and long-held identity as responsible and risk-averse, she knows it's not just money that's standing between her and her dreams. On set, Tori immediately catches the eye of Kendra Campbell, the notoriously ruthless (and terminally single) celebrity chef and Bake-o-Rama judge. Kendra is desperate to save her beloved restaurant and expand her Chippy Chunk cookie empire, and the show is her ticket to financial security. But, as both her brother and the programming VP inform her, she needs to soften her approach in order to appease viewers seeking a feel-good time. After years spent fighting for space in a male-dominated industry, Kendra finds it challenging-and surprisingly rewarding-to make the shift from harsh critique to encouragement and support. Can she take the same approach to her love life?